Assessment of thiamine status and its association with clinical parameters in patients undergoing maintenance hemodialysis - Yang, Bo; Lan, Naiying; Zeng, Fanzhou; Shao, Qing; Ye, Dan; Wang, Hao; Xue, Cheng; Liu, Nanmei (Frontiers in Nutrition, 2025)
ObjectiveThiamine deficiency is a common complication in end-stage renal disease (ESRD) patients receiving maintenance hemodialysis (HD). The purpose of this cross-sectional study was to assess the prevalence of thiamine deficiency in HD patients and its association with clinical parameters.MethodsThis was a single-center cross-sectional study that included 113 maintenance HD patients from our hospital. Thiamine status was evaluated by high-performance liquid chromatography on whole blood samples. We evaluated the association between blood thiamine concentration and other clinical parameters, including markers of iron metabolism and cardiac function.ResultsThe prevalence of thiamine deficiency was 11.5%. Univariate analysis revealed a significant positive correlation between thiamine levels and iron metabolism markers, including hemoglobin level (Rho = 0.257, p = 0.006), transferrin saturation (Rho = 0.244, p = 0.009), and serum iron (Rho = 0.213, p = 0.025). A multivariate regression analysis confirmed that thiamine levels were independently associated with hemoglobin levels (beta coefficients = 0.25, p = 0.012).ConclusionThese findings suggest an association between lower thiamine levels and anemia in HD patients. Further research is needed to elucidate the underlying mechanisms and evaluate the efficacy of thiamine supplementation in improving anemia and other clinical outcomes in this population.